2005
DOI: 10.1002/j.2050-0416.2005.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on ATP Production of Lactic Acid Bacteria in Beer and Development of a Rapid Pre-Screening Method for Beer-Spoilage Bacteria

Abstract: Three beer-spoilage strains of lactic acid bacteria (LAB), Lactobacillus brevis ABBC45, L. lindneri DSM 20690 T and L. paracollinoides DSM 15502 T , exhibited strong ATP-yielding ability in beer. To investigate energy sources, these beer-spoilage strains were inoculated into beer. After the growth of the strains in beer, utilized components were determined by high performance liquid chromatography (HPLC). As a result, it was shown that citrate, pyruvate, malate and arginine were consumed by beer-spoilage LAB s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
(73 reference statements)
0
15
0
4
Order By: Relevance
“…Amino acid metabolism. The hop adaptation of L. brevis TMW 1.465A increased the conversion of arginine to ornithine via the ADI pathway (42). The observations concerning the levels of metabolites were substantiated by quantification of the expression of the enzymes of the ADI pathway.…”
Section: Discussionmentioning
confidence: 81%
“…Amino acid metabolism. The hop adaptation of L. brevis TMW 1.465A increased the conversion of arginine to ornithine via the ADI pathway (42). The observations concerning the levels of metabolites were substantiated by quantification of the expression of the enzymes of the ADI pathway.…”
Section: Discussionmentioning
confidence: 81%
“…It should also be noted that these hop resistance mechanisms are energy-consuming in nature and may give an extra burden to beer spoilage LAB strains when overexpressed. It was further reported that LAB strains are more dependent on the metabolism of organic acids and amino acids in beer rather than fermentable carbohydrates 32 . Therefore the altered metabolism in beer spoilage LAB can conceivably contribute to the induction of VNC states.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these disadvantages, beer spoilage LAB strains are still capable of growth in beer. Indeed three beer spoilage LAB strains, L. brevis ABBC45, L. lindneri DSM 20690 T and L. paracollinoides JCM 11969 T , were found to exhibit strong ATP-yielding ability in beer 145 . In addition, the ATP pool in the hop-resistant LAB strains was found to be larger than in the hop-sensitive strains 129 .…”
Section: Part 2: Hop Resistance In Beer Spoilage Labmentioning
confidence: 99%
“…It was shown that citrate, pyruvate, malate and arginine were consumed to support the growth of the beer spoilage LAB strains 145 . The four components induced considerable ATP production, even in the presence of hop compounds, accounting for the ATP-yielding ability of the beer spoilage LAB strains observed in beer.…”
Section: Part 2: Hop Resistance In Beer Spoilage Labmentioning
confidence: 99%